The politics of European sales law : a legal-political inquiry into the drafting of the uniform commercial code, the Vienna Sales Convention, the Dutch Civil Code and the European Consumer Sales Directive in the context of the Europeanization of contract Law /: a legal-political inquiry into the drafting of the uniform commercial code, the Vienna Sales Convention, the Dutch Civil Code and the European Consumer Sales Directive in the context of the Europeanization of contract Law. (2008) - Unknown
No abstract available